The Role of Transactional Leadership on Work Engagement and Workload as a Moderator for Business Process Outsourcing Company - Raden Ajeng Claudia Yessie Dewi Sekartaji; Indrayanti, Indrayanti (International Journal of Social Science and Business, 2025)
Startup companies are looking at Business Process Outsourcing to help provide employees quickly and with quality. If the company holds it themselves, there will be many costs involved in the selection process. Companies in this business themselves are ultimately required to be able to maintain work engagement even though they have a high workload. This research aims to look at the role of transactional leadership in the work engagement of business process outsourcing employees with workload as a moderator. This research is quantitative research with a survey method. This research involved one hundred twenty employees at a business process company. Data were analyzed using PLS SEM 4.0. The research results show that, in general, workload is proven to moderate the relationship between transactional leadership and work engagement. Individuals who perceive their workload as low will have high work engagement if their transactional leadership is high. Meanwhile, individuals who perceive their workload as high have no difference in their perception of high or low transactional leadership and high or low work engagement. The study emphasizes balancing workload and leadership style in BPO settings. Transactional leadership enhances engagement under manageable workloads, but its effect weakens in high-pressure environments, indicating the need for alternative strategies.